Pengaruh Implementasi Role Playing dan Buah Roh Terhadap Peminimalisiran Bullying di SMP Swasta Masehi Medan Tahun 2021 - Fitri Irda Notalya Gulo (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study aims to determine 1) the effect of role-playing implementation on the minimization of bullying. 2) The effect of implementing the fruit of the Spirit on the minimization of bullying. 3) The effect of implementing role-playing and the fruit of the Spirit together on the minimization of bullying. This study uses a quantitative descriptive method with a population of all students in grades VII-IX of SMP Swasta Masehi Medan with a total of 63 people with a sample of 31. Data was collected through the help of google workspace so that the answers to the questionnaire of all variables were obtained well analyzed through the SPSS 22 computer program. The results of data analysis concluded that 1) Minimizing bullying by implementing the role had an effect of 17.60% and another 82.40% influenced by other factors. Based on that, the hypothesis is accepted with a count of 3.624. 2) The fruit of the Spirit can influence the minimization of bullying by 18.10%, and other factors influence 81.90%. In connection with that, the hypothesis is accepted with a count of 4.243. 3) There is a positive and significant effect between the implementation of role-playing and the fruit of the Spirit on the minimization of bullying is 35.30%. And 64.70% were influenced by other factors. In connection with that, the hypothesis is accepted with a count of 17,004. Role-playing helps students experience the circumstances of others based on the roles played to practice the Fruit of the Spirit to give understanding and awareness to themselves to be kind to friends in their association.